FAKTOR-FAKTOR YANG MEMENGARUHI MINAT GENERASI Z BERPROFESI SEBAGAI PETANI DI KECAMATAN MERAWANG KABUPATEN BANGKA - Sitorus, Rostiar; Fahrozi, Muhammad Diego; Purwasih, Rati (Program Studi Magister Ilmu Pertanian, Fakultas Pertanian, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2023)
This study aims to identify the interest of generation Z in working as farmers and analyze the factors that influence generation Z's interest in working as farmers in Merawang District, Bangka Regency. This research was conducted from November 2021 to February 2022 in Merawang District, Bangka Regency. The research method used is the survey method. The sampling method used is quota sampling with generation Z samples whose parents work as farmers in Merawang District. The number of samples of one hundred generation Z whose parents work as farmers in Merawang District. The data analysis method uses qualitative descriptive analysis and binary logistic regression. The results showed that generation Z's interest in working as farmers was 71.4% with a high category Factors that influence generation Z's interest in working as farmers that have a significant effect are parents' farming income, the distance of the house from the urban center, the number of social media ownership and gender.